2021
DOI: 10.1002/celc.202101105
|View full text |Cite
|
Sign up to set email alerts
|

A Chemical Evolution‐Like Method to Synthesize a Water‐Oxidizing Catalyst

Abstract: The development of new procedures for synthesizing new, low‐cost, and stable metal oxides for the oxygen‐evolution reaction (OER) by water oxidation is critical. Since the 2000s, there has been a rapid rise in the use of first‐row transition metal (hydr)oxides for the OER. However, there is still a need to design and synthesize an efficient and stable catalyst for the OER. The present paper aims to design and synthesize an OER catalyst based on “a look at nature” strategy. In a simple and chemical evolution‐li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…It is suggested that the Ni coordination compound species form aggregations of molecular species before the decomposition and then decompose to Ni (hydr)­oxide. Different methods have been reported for synthesizing OER catalysts, and the decomposition of metal coordination compounds is also a promising method for this purpose.…”
Section: Results and Discussionmentioning
confidence: 99%
“…It is suggested that the Ni coordination compound species form aggregations of molecular species before the decomposition and then decompose to Ni (hydr)­oxide. Different methods have been reported for synthesizing OER catalysts, and the decomposition of metal coordination compounds is also a promising method for this purpose.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Some research groups investigated the effects of other ions on layered Mn oxide to investigate its structure or catalytic activity. These effects include inducing Mn­(III), modifying the chemical and electronical properties of layered Mn oxide, enhancing charge mobility, and tuning the electronic structure. …”
Section: Introductionmentioning
confidence: 99%
“…Different synthesis methods were used, and it was confirmed that various ions could increase the WOR. …”
Section: Introductionmentioning
confidence: 99%